The genome sequence of White-foot Bell moth, Epiblema foenella (Linnaeus, 1758) [version 1; peer review: 2 approved] - Phil Smith; James Hammond (Wellcome Open Research)
We present a genome assembly from an individual female Epiblema foenella (White-foot Bell moth; Arthropoda; Insecta; Lepidoptera; Tortricidae). The genome sequence has a total length of 649.80 megabases. Most of the assembly (99.96%) is scaffolded into 28 chromosomal pseudomolecules, including the Z and W sex chromosomes. The mitochondrial genome has also been assembled and is 15.99 kilobases in length.